Remote versus face-to-face fall risk assessment in home dwelling older adults: a reliability study - Toledano-Shubi, Adi; Hel-Or, Hagit; Sarig Bahat, Hilla (Physiotherapy theory and practice, 2025)
Falls are a leading cause of severe injury and death in older adults. Remote screening of fall risk may prevent falls and hence, advance health and wellness of older adults. While remote health care is becoming a common practice, we question if remote evaluation of fall risk is as reliable as face-to-face (FTF). To assess the inter-tester reliability of synchronized remote and FTF fall risk assessment. This inter-format, inter-rater reliability study included 48 home dwelling older adults aged 65 and over. Five valid functional and balance tests were conducted: 30 Second Sit-to-Stand (STS), MiniBESTest, Timed up and go (TUG), 4-Meter Walk (4MWT), and Berg Balance Scale (BBS). Instructions were provided via videoconferencing, and two physiotherapists scored performance simultaneously, one remotely, and one in the room. Inter-rater reliability between remote and FTF scores was analyzed using intraclass correlation coefficient (ICC ), standard error of measurement (SEM), minimal detectable change (MDC ) and Bland and Altman analysis. Excellent ICCs were found for STS, MiniBESTest, TUG, and BBS (0.90-0.99), and moderate for 4MWT (0.74). SEM and MDC values were STS (0.37,1.03 repetitions), MiniBESTest (1.43,3.97 scores), TUG (1.22,3.37 seconds), 4MWT (0.17,0.47 m/second), and BBS (1.79,4.95 scores). The Bland and Altman analysis showed excellent agreement between remote and FTF assessments of the STS. All other tests showed low to moderate agreement. Mean difference ± SD and 95%LOA were as follows: STS (-0.11 ± 0.52), (-1.13,0.91) repetitions, MiniBESTest (0.45 ± 1.98), (-3.43,4.32) scores, TUG (-0.35 ± 1.54), (-3.37,2.67) seconds, 4MWT (-0.08 ± 0.22), (-0.35,0.51) meter/second, and BBS (0.04 ± 2.53), (-4.93,5.01) scores. The findings support the responsible integration of remote fall risk assessment in clinical practice, enabling large-scale screenings and referrals for early intervention to promote healthy aging and fall prevention.